Coastal Erosion as a Major Sediment Source in the Inner Gulf of Thailand: Implications for Carbon Dynamics in Tropical Coastal Ocean Systems - Bingbing Wei; Stephanie Kusch; Till J. J. Hanebuth; Limin Hu; Miao Fan; Guodong Jia; Gesine Mollenhauer; Moritz Holtappels (Geophysical Research Letters)
Abstract Coastal erosion is an increasingly dominant sediment source in marginal seas, particularly in low‐lying areas affected by deltaic subsidence and sediment deficits from upstream water management. However, its role in sediment and organic carbon (OC) dynamics remains to be estimated. Our analyses of the inner Gulf of Thailand (IGoT) revealed that riverine sediment fluxes decreased from 6.6 to 5.4 Mt/yr after 1975, while sediment accumulation within the IGoT increased from 20.8 to 29.5 Mt/yr. The observed trend indicates major sediment contributions from coastal erosion, particularly from mangrove deposits. This process destabilizes coastal ecosystems and accelerates OC decomposition, that is, a low burial efficiency (16.8 ± 5.5%) leads to CO2 release. Extrapolating these findings globally, mangrove loss could release ∼175 Tg/yr CO2. As coastal erosion intensifies under sea‐level rise and human land‐use practices, preserving coastal ecosystems is critical for mitigating blue carbon loss and maintaining coastal stability and resilience.